Hypertensive disorders in women with peripartum cardiomyopathy: insights from the ESC EORP PPCM Registr - Alice M Jackson; Mark C Petrie; Alexandra Frogoudaki; Cécile Laroche; Finn Gustafsson; Bassem Ibrahim; Alexandre Mebazaa; Mark R Johnson; Petar M Seferovic; Vera Regitz-Zagrosek; Amam Mbakwem; Michael Böhm; et al. (John Wiley & Sons Ltd on behalf of European Society of Cardiology, 2021)
Hypertensive disorders occur in women with peripartum cardiomyopathy (PPCM). How often hypertensive disorders co-exist, and to what extent they impact outcomes, is less clear. We describe differences in phenotype and outcomes in women with PPCM with and without hypertensive disorders during pregnancy. Methods and results: The European Society of Cardiology EURObservational Research Programme PPCM Registry enrolled women with PPCM from 2012-2018. Three groups were examined: (i) women without hypertension (PPCM-noHTN); (ii) women with hypertension but without pre-eclampsia (PPCM-HTN); (iii) women with pre-eclampsia (PPCM-PE). Maternal (6-month) and neonatal outcomes were compared. Of 735 women included, 452 (61.5%) had PPCM-noHTN, 99 (13.5%) had PPCM-HTN and 184 (25.0%) had PPCM-PE. Compared to women with PPCM-noHTN, women with PPCM-PE had more severe symptoms (New York Heart Association class IV in 44.4% vs. 29.9%, P < 0.001), more frequent signs of heart failure (pulmonary rales in 70.7% vs. 55.4%, P = 0.002), a higher baseline left ventricular ejection fraction (LVEF) (32.7% vs. 30.7%, P = 0.005) and a smaller left ventricular end-diastolic diameter (57.4 ± 6.7 mm vs. 59.8 ± 8.1 mm, P = 0.001). There were no differences in the frequencies of death from any cause, rehospitalization for any cause, stroke, or thromboembolic events. Compared to women with PPCM-noHTN, women with PPCM-PE had a greater likelihood of left ventricular recovery (LVEF ≥ 50%) (adjusted odds ratio 2.08, 95% confidence interval 1.21-3.57) and an adverse neonatal outcome (composite of termination, miscarriage, low birth weight or neonatal death) (adjusted odds ratio 2.84, 95% confidence interval 1.66-4.87). Conclusion: Differences exist in phenotype, recovery of cardiac function and neonatal outcomes according to hypertensive status in women with PPCM.
Hypertensive disorders occur in women with peripartum cardiomyopathy (PPCM). How often hypertensive disorders co-exist, and to what extent they impact outcomes, is less clear. We describe differences in phenotype and outcomes in women with PPCM with and without hypertensive disorders during pregnancy.
Keywords: Heart failure; Hypertension; Peripartum cardiomyopathy; Pre-eclampsia; Pregnancy